2022
DOI: 10.3389/fphar.2022.835697
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor NR4A2 Is Constitutively Expressed in Cartilage and Upregulated in Inflamed Synovium From hTNF-Alpha Transgenic Mice

Abstract: Orphan nuclear receptor 4A2 (NR4A2/Nurr1) is a constitutively active transcription factor with potential roles in the onset and progression of inflammatory arthropathies. NR4A2 is overexpressed in synovium and cartilage from individuals with rheumatoid arthritis (RA), psoriatic arthritis, and osteoarthritis. This study documents the expression and tissue localization of NR4A2 and upstream regulator nuclear factor kappa B (NF-κB) in the human tumor necrosis factor-alpha (hTNF-α) transgenic mouse model of RA. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Meanwhile, the heatmap of H3K27ac signal intensity also showed that NaBu restored the increased H3K27ac occupancy caused by DON in ROS and TNF-α pathways (Figure B,D). Notably, the nuclear receptor NR4A2 is a promising therapeutic target in the TNF-α signaling pathway and has a mechanistic link with OS. , Therefore, we aimed to explore whether NR4A2 is involved in the ROS and TNF-α processes regulated by NaBu. STRING analysis revealed that NR4A2 was associated with the key genes in the ROS and TNF-α pathways (Figure E).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the heatmap of H3K27ac signal intensity also showed that NaBu restored the increased H3K27ac occupancy caused by DON in ROS and TNF-α pathways (Figure B,D). Notably, the nuclear receptor NR4A2 is a promising therapeutic target in the TNF-α signaling pathway and has a mechanistic link with OS. , Therefore, we aimed to explore whether NR4A2 is involved in the ROS and TNF-α processes regulated by NaBu. STRING analysis revealed that NR4A2 was associated with the key genes in the ROS and TNF-α pathways (Figure E).…”
Section: Resultsmentioning
confidence: 99%